2014
DOI: 10.1186/1756-0500-7-266
|View full text |Cite
|
Sign up to set email alerts
|

High rates of early treatment discontinuation in hepatitis C-infected US veterans

Abstract: BackgroundPatients with chronic hepatitis C (HCV) frequently discontinued dual therapy with pegylated interferon alfa (Peg-IFN) plus ribavirin (RBV) before reaching the recommended duration of 48 or 24 weeks for genotypes (G) 1/4 or 2/3, respectively. We quantified rates of discontinuation despite efficacy (non-LOE) versus lack of efficacy (LOE) versus discontinuation for unknown reasons in a national database of United States veterans.MethodsWe identified a population-based cohort of U.S. veterans with encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Our results are very encouraging, as DAA therapy is associated with high cure rates, few side effects, and a decrease in adverse liver‐related outcomes, unlike earlier HCV interferon‐based therapies, which carried lower cure rates probably as a result of the high side‐effect profile of interferon leading to high discontinuance of treatment prior to cure . Interestingly, unlike our results, a recent report indicated that DAA treatment was associated with an unexpected high rate of HCC .…”
Section: Discussionsupporting
confidence: 54%
“…Our results are very encouraging, as DAA therapy is associated with high cure rates, few side effects, and a decrease in adverse liver‐related outcomes, unlike earlier HCV interferon‐based therapies, which carried lower cure rates probably as a result of the high side‐effect profile of interferon leading to high discontinuance of treatment prior to cure . Interestingly, unlike our results, a recent report indicated that DAA treatment was associated with an unexpected high rate of HCC .…”
Section: Discussionsupporting
confidence: 54%
“…Another commonly used definition for adherence was to achieve >80% rate of treatment completion and >80% receipt of the prescribed treatment regimens. Despite which definition used while treating patients with CH‐C, adherence to the full regimen is important to optimise the efficacy of anti‐viral therapy . Furthermore, adherence to the treatment regimen will become even more important when drugs are approved and are utilised in the “real world” setting.…”
Section: The Role Of Treatment Regimen Adherence and Pro'smentioning
confidence: 99%
“…Other drivers of non‐adherence that are specific to patients include less than 12 years of education, history of incarceration, current alcohol and drug use, and failure to show for follow‐up appointments . In addition, treatment‐associated fatigue and impairment of HRQOL during treatment can predict non‐adherence .…”
Section: The Role Of Treatment Regimen Adherence and Pro'smentioning
confidence: 99%
“…Achieving a sustained virological response with antiviral therapy (SVR, defined as undetected HCV RNA measured at 12‐ or 24‐week post‐treatment) is associated with lower risk of developing hepatocellular cancer (HCC) and lower all‐cause mortality in patients with advanced fibrosis . With the prior standard of care HCV therapy of pegylated interferon combined with ribavirin, however, less than half of GT1 patients achieved SVR, and real‐world evidence underscores the suboptimal adherence to this regimen …”
Section: Introductionmentioning
confidence: 99%